Effect of Montmorillonite Incorporation on Wettability of Heat-Cured Soft-Denture Lining Material - Safa Abbas M. A. Feiruz 1 * , Wasmaa Sadik Mahmood 2 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Relining is the process of resurfacing the intaglio of a removable dental prosthesis with an entirely fresh base material, generating a precise adaptation to the denture base area. The wetting ability of a denture material gives an indication of the extent to which the lubricating effect of saliva will be enhanced, that promoting retention of denture and patient comfort . The purpose of this research was to evaluate how adding montmorillonite nanoparticles(MMTNPs) would affect the soft lining material’s wettability. Materials and Methods: (MMTNPs) with 0.25 and 0.5 wt. of % were incorporated into the heat-cured acrylic-based soft lining. A total of thirty specimens were prepared for wettability test ,ten for each concentration (0%,0.25%,0.5% wt.MMTNPs) .Also specimens for atomic force microscope (AFM). The data were analyzed using one-way ANOVA test and the Bonferroni multiple comparison test. Result: The wettability was not significantly decreased as a result. Conclusion: The present study showed that MMTNPs decrease the wettability of soft lining materials.